URGENSI IMPLEMENTASI KURIKULUM MERDEKA DALAM PEMULIHAN PEMBELAJARAN - Ibnu, Ibnu; Irtati, Irtati; Maryani, Baiq; Anwar, Khairil; Sulfana, Evi Yanti (Universitas Muhammadiyah Mataram, 2024)
Currently, the word